GAMBARAN TINGKAT PENGETAHUAN DAN PELAKSANAAN PRAKTEK CUCI TANGAN PAKAI SABUN PADA SISWA KELAS 12 PESANTREN ALIYAH AS’AD KOTA JAMBI - Putri, Nadhilah; Ratna Sugiati; Erny Kusdiyah; Darmawan, Armaidi (Scientific Of Environmental Health and Diseases, 2024)
Background: Handwashing with soap is one of the National Community-Based Total Sanitation Movements that aims to increase awareness, willingness, and ability to live a healthy life for every individual in order to realize an optimal degree of public health. Health is an investment to support economic development and has an important role in poverty reduction efforts, Therefore, improving the degree of health needs to be done promotively and preventively by empowering the community through clean and healthy living behavior which is implemented in five settings, namely: households, educational institutions, workplaces, public places and health service facilities. Method: A mixed-method in the form of interviews with the person in charge of clean and healthy living behavior programs and health promotion and on students of Pesantren Aliyah As'ad Jambi City and questionnaires for grade 12 students of Pesantren Aliyah As'ad Jambi City. Results: The level of knowledge of students at Pesantren Aliyah As'ad Jambi City about handwashing with soap shows a good category with a percentage of 100%, the implementation of handwashing with soap (CTPS) practices for students at Pesantren Aliyah As'ad Jambi City which is quite blessed at 58%, good category as much as 29% and less category as much as 13% Conclusion: The knowledge of Aliyah As'ad Islamic Boarding School students about CTPS is good, while the implementation of CTPS is still not good with a sufficient score of 58% and a score of less than 13%.